Ultrasensitive Ultraviolet Chiral Plasmonic Biosensor Based on Passivated Al Shells - Huang, Shanshan; Wang, Siyi; Yang, Xiu; Görlitzer, Eric; Peng, Jialong; Liu, Zhuang; Chikkaraddy, Rohit; Du, Jinglei; Vogel, Nicolas; Hou, Yidong (ACS Applied Materials and Interfaces, 2025)
Chiroptical spectroscopic techniques offer a nondestructive means of elucidating the stereochemical structures of biomolecules and have demonstrated significant applications across diverse fields, including bioscience, biomedicine, and clinical diagnosis, among others. However, the inherently weak chiroptical effects exhibited by natural chiral molecules pose a significant challenge to detection sensitivity. In this study, we demonstrate an ultrasensitive ultraviolet chiral plasmonic biosensor (CPB) that leverages a self-assembled metasurface composed of passivated aluminum chiral shells (ACSs). By meticulously optimizing the geometry and size of these shells, we achieve a uniform, large, and readily accessible superchiral field on the top surface of the ACSs, thereby enhancing their interaction with chiral biomolecules. In addition, the abundant surface lattice resonance (SLR) modes excited in the ultraviolet waveband narrow the chiroptical resonance peaks and improve the identifiability of sensor pointers. In experiments, large-area ACSs with strong chiroptical effects were realized by depositing Al on a colloidal monolayer with hexagonal order and then passivating it with ozone to improve stability. When immersed in solutions containing chiral molecules, the g-factor maxima of the ACSs exhibit a notable peak shift that correlates with both the stereochemical structures and the concentrations of the biomolecules. Notably, the consistency chiral sensor parameter U reaches 10.9095 for the null point and 0.1739 for peaks of g-factor spectra, which makes a record in the field CPBs. The systematic analysis of the SLR modes, superchiral field, and chiral sensor parameters further rationalizes the record chiral sensor performance realized in this work.
CRIS-Team Scopus Importer:2025-05-09
Keywords: chiral biosensor; chiral field; chiroptical effect; glancing angle deposition; microsphere lithography; ultraviolet chiral metamaterials